Participant‐Driven Matchmaking in the Genomic Era. Issue 10 (27th August 2015) - Lambertson, Katherine F.; Damiani, Stephen A.; Might, Matthew; Shelton, Robert; Terry, Sharon F.
<x xml:space="preserve">Abstract</x> Genomic matchmaking networks, which seek to link patients with similar genotypes and/or phenotypes, play an important role in confirming diagnoses made by whole‐genome and ‐exome sequencing. We argue that matchmaking efforts led by affected individuals and their families provide a unique opportunity to greatly increase the size of these networks, and simultaneously increase the quantity and specificity of available data. We propose a participant‐led technology solution to scale participant‐led efforts, known as the Platform for Engaging Everyone Responsibly (PEER).